2010
DOI: 10.1103/physreve.81.036101
|View full text |Cite
|
Sign up to set email alerts
|

Structure and control of self-sustained target waves in excitable small-world networks

Abstract: Small-world networks describe many important practical systems among which neural networks consisting of excitable nodes are the most typical ones. In this paper we study self-sustained oscillations of target waves in excitable small-world networks. A dominant phase-advanced driving (DPAD) method, which is generally applicable for analyzing all oscillatory complex networks consisting of nonoscillatory nodes, is proposed to reveal the self-organized structures supporting this type of oscillations. The DPAD meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 20 publications
2
67
1
1
Order By: Relevance
“…4(a), this network owns two reflection symmetries: S 1 and S 2 . A checking of their eigenvalues shows that only S 1 satisfies the eigenvalue condition λ = 0.5, to make the pattern stable, the coupling strength should be chosen within the range ε ∈ (12,20). By ε = 12.8, we plot in Fig.…”
Section: (D)mentioning
confidence: 99%
See 2 more Smart Citations
“…4(a), this network owns two reflection symmetries: S 1 and S 2 . A checking of their eigenvalues shows that only S 1 satisfies the eigenvalue condition λ = 0.5, to make the pattern stable, the coupling strength should be chosen within the range ε ∈ (12,20). By ε = 12.8, we plot in Fig.…”
Section: (D)mentioning
confidence: 99%
“…For instance, it is found that by intentionally removing a few of the network links at the beginning of the cascading, the network damage can be largely reduced [6]. Besides cascading, recently the idea of topological control has been also employed in many other problems in network science, e.g., epidemic propagation [7], global synchronization [8], oscillatory patterns [9], and control optimization [10], etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Network connections of nonoscillatory elements, for instance, give rise to such dynamics and have been studied in various contexts, including gene networks [1], epidemic spreading dynamics [2][3][4][5], and generic excitable units [6][7][8][9][10], Excitable units undergo oscillations in many ways: Simple two excitable systems can exhibit sustained dynamics when delay-coupled [11]; spatially extended excitable media can produce sustained spiral waves by introducing a perturbation leading to the formation of a spiral core [12]; one can even consider interactions at a distance through nonlocal links embedded in spatially extended systems [13][14][15][16], which eventually forms network structures composed of wave propagation and nonlocal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous papers [16,17], we proposed a dominant phase-advanced driving (DPAD) method to reveal the underlying dynamic structure of self-sustained target waves in small-world networks of excitable nodes. Based on the information embedded in the DPAD structures, we successfully revealed the oscillation source.…”
Section: Introductionmentioning
confidence: 99%